Optimasi Penentuan Rute Pendistribusian dengan Penambahan Variabel Waktu Tempuh pada Algoritma Nearest Neighbor - Millati Izzatillah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The Nearest Neighbor algorithm is a method of determining routes by visiting the closest customer to the depot or agent. Customer become the starting point for visiting the next customer with the closest distance to the last customer visited and the process is carried out continuously until the distribution process ends, and return to the depot or agent. Because it focuses on the closest distance, the Nearest Neighbor Algorithm does not take into account the travel time between points which in reality does not mean that the shortest distance has a shorter travel time. The purpose of this study is to test the Nearest Neighbor Algorithm by calculating the travel time. Creation route is based on the route with the shortest distance and the route with the fastest time. These routes can be a decision to optimize the distribution of LPG Gas PT. Asri Dena Pertiwi and minimize distribution costs. Testing the Nearest Neighbor Algorithm by adding the travel time variable was successfully carried out with the results of calculating the travel time in determining the route using the Nearest Neighbor Algorithm making the route creation more optimal than before. Savings were also obtained because the operational time was 35 minutes faster and the expenditure cost was Rp. 110,291